Id Proteins Suppress E2A-Driven Invariant Natural Killer T Cell Development prior to TCR Selection - Roy, Sumedha; Moore, Amanda J.; Love, Cassandra; Reddy, Anupama; Rajagopalan, Deepthi; Dave, Sandeep S.; Li, Leping; Murre, Cornelis; Zhuang, Yuan (Frontiers in Immunology, 2018)
A family of transcription factors known as E proteins, and their antagonists, Id proteins, regulate T cell differentiation at critical developmental checkpoints. Id proteins promote the differentiation of conventional αβ T cells, and suppress the expansion of innate-like αβ T cells known as invariant Natural Killer T (iNKT) cells. However, it remains to be determined whether Id proteins differentially regulate these distinct lineage choices in early stages of T cell development. In this manuscript, we report that in Id-deficient mice, uninhibited activity of the E protein family member E2A mediates activation of genes that support iNKT cell development and function. There is also biased rearrangement in Id-deficient DP cells that promotes selection into the iNKT lineage in these mice. The observed expansion of the iNKT cells is not abrogated by blocking pre-TCR signaling, which is required for conventional αβ T cell development. Finally, E2A is found to be a key transcriptional regulator of both iNKT and γδNKT lineages, which appear to have shared lineage history. Therefore, our study reveals a previously unappreciated role of E2A in coordinating the development of the iNKT lineage at an early stage, prior to their TCR-mediated selection alongside conventional αβ T cells.